Nitric Oxide and Hydrogen Peroxide Mediate Wounding-Induced Freezing Tolerance through Modifications in Photosystem and Antioxidant System in Wheat - Si, Tong; Wang, Xiao; Wu, Lin; Zhao, Chunzhao; Zhang, Lini; Huang, Mei; Cai, Jian; Zhou, Qin; Dai, Tingbo; Zhu, Jian-Kang; Jiang, Dong (Frontiers in Plant Science, 2017)
Mechanical wounding is a common stress caused by herbivores or manual and natural manipulations, whereas its roles in acclimation response to a wide spectrum of abiotic stresses remain unclear. The present work showed that local mechanical wounding enhanced freezing tolerance in untreated systemic leaves of wheat plants (Triticum aestivum L.), and meanwhile the signal molecules hydrogen peroxide (H2O2) and nitric oxide (NO) were accumulated systemically. Pharmacological study showed that wounding-induced NO synthesis was substantially arrested by pretreatment with scavengers of reactive oxygen species and an inhibitor of NADPH oxidase (Respiratory burst oxidase homolog, RBOH). On the contrary, wounding-induced H2O2 accumulation was not sensitive to NO synthetic inhibitors or scavenger, indicating that H2O2 acts upstream of NO in wounding signal transduction pathways. Cytochemical and vascular tissues localizations approved that RBOH-dependent H2O2 acts as long-distance signal in wounding response. Transcriptome analysis revealed that 279 genes were up-regulated in plants treated with wounding and freezing, but not in plants treated with freezing alone. Importantly, freezing- and wounding-induced genes were signiﬁcantly enriched in the categories of “photosynthesis” and “signaling”. These results strongly supported that primary mechanical wounding can induce freezing tolerance in wheat through the systemic accumulation of NO and H2O2, and further modifications in photosystem and antioxidant system.